Municipal Own-Source Revenues in Times of the COVID-19 Pandemic - Życzkowska, Elżbieta; Dziuba, Jarosław (Dochody własne gmin w Polsce w dobie pandemii COVID-19, 2023)
Own-source revenues represent one of the most important funding sources for municipalities in Poland. Such revenues cover all types of municipal receipts excluding subsidies and special purpose grants from the state budget. The purpose of the article was to assess the impact of the COVID-19 pandemic on municipal own-source revenues in the period 2020-2021. A comparative analysis method was used to assess this impact. The analyses were based on the revenue figures for 2020- -2021 (planned and received) as well as the figures for the year preceding the pandemic, i.e. 2019. The aggregate figures available on www.mf.gov.pl – reports on the implementation of local government budgets – constituted the main source of data. The conducted analysis showed that the first year of the pandemic was better than expected in terms of municipalities, as municipal revenues increased in Poland during this period. This resulted from the funding from the Central Governmental Fund for Local Investments (CGFLI) and qualifying these funds as own-source revenues. Rural municipalities benefited the most in this case. The scale of lost revenues as a result of fiscal power instruments applied by the municipalities was not significant.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2023; vol. 67, nr 2, s. 170-177
Keywords: local government finance; own-source revenues; COVID-19 pandemic; finanse samorządu terytorialnego; dochody własne; pandemia COVID-19